Recording of vital signs in a district general hospital emergency department. Issue 12 (25th November 2008) - Armstrong, B; Walthall, H; Clancy, M; Mullee, M; Simpson, H
Abstract : Aim: To examine and explore factors that may influence the recording of vital signs in adult patients within the initial 15 min and again within 60 min of arrival in the "resuscitation" and "major" areas of the emergency department (ED). Methods: A retrospective analysis of recording of vital signs was performed on 400 consecutive sets of notes from adult patients presenting to the "major" or "resuscitation" areas of a district general hospital ED. The effect of staffing levels, triage category and attendances on the recording of vital signs was examined using logistic regression. The main outcome measures were the proportion of patients with all vital signs recorded within 15 min of arrival, the proportion of patients with all vital signs repeated within 60 min of arrival and the outcomes of logistic regression analysis. Results: Only 223/387 patients (58%) had all vital signs recorded within 15 min of arrival and only 29/387 (7%) had all vital signs repeated at 60 min. There was a significant relationship between the failure to record vital signs and lower triage categories. There was no evidence that staffing levels or number of attendances predicted the recording of vital signs within 15 min of arrival. Conclusion: Recording of vital signs was poor and unrelated to staffing levels or numbers of patients attending the ED. Failure to record patients' vital signs undermines strategies to detect and manage ill patients.